Determinan Persepsi Mahasiswa Mengenai Penggelapan Pajak dengan Penerapan Teknologi Informasi sebagai Variabel Moderasi - Latifah, Jihan; Yeni, Fitri; Permata Sari, Putri Intan (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The aim of this research is to determine the factors that have an impact on students' views regarding tax evasion with the application of information technology as a moderating variable. The sample in this research is accounting students class of 2020 concentrating on taxation at Putra Indonesia University "YPTK" Padang. The selection of students as samples was based on the reason that they represent the future generation of taxpayers. The aim is to contribute to reducing tax evasion behavior, overcoming various practices that deviate from tax obligations. The sampling technique for this research used convenience sampling. Respondents in this study totaled 128 respondents. Data analysis using multiple linear regression with SPSS 26 tools. Based on the findings, it was found that tax justice and tax discrimination had a positive and significant impact on students' perceptions or views regarding tax evasion, but not the tax system. IT as a moderating variable has a partial moderating influence on the relationship between tax justice and students' perceptions or views regarding tax evasion. However, it cannot moderate the influence of the tax system and tax discrimination on student perceptions or views regarding tax evasion among accounting students with a tax concentration class of 2020 at UPI "YPTK" Padang.